Analysis of enzyme activity and microbial community structure changes in the anaerobic digestion process of cattle manure at sub-mesophilic temperatures - Zhen Xiaofei; Luo Miao; Dong Haiying; Fang Lei; Wang Weiwei; Feng Lei; Yu Qin (Green Processing and Synthesis, 2021)
To improve the biogas potential in anaerobic digestion of cattle manure in cold regions, we investigated, in this study, the potential of the anaerobic digestion of cattle manure through sequencing batch anaerobic digestion experiments at sub-mesophilic temperatures (15°C, 20°C, 25°C, and 37°C) for 50 days. Specifically, the changes in the biogas yield, pH, sCOD concentration, enzyme activity, and microbial community structure were examined. The maximum daily yield of biogas was 19.18 mL·gVS−1, which was recorded on day 6 at 37°C, and the final biogas accumulation yield at this temperature was 403.64 mL·gTS−1. The concentration of sCOD gradually increased as enzyme activity increased. The maximum activities of cellulase, hemicellulase, protease, and amylase were recorded in the 37°C experimental group. The decrease in temperature severely limited the activity of different types of enzymes, resulting in a decrease in the activity of microorganisms, which greatly influenced the methanogenic reaction. The dominant bacteria at the phylum level were Bacteroidetes and Proteobacteria, and the dominant methanogen at the genus level was Methanosaeta.